Contemporary Analysis of Economic Multipliers in the Jordanian Economy: An Updated Input-Output Approach - MASHAQBEH, Hamza Mohammed; AL-ABABNEH, Hassan Ali; AT-TARAWNEH, Anas Taleb; AL-SMEIRAN, Mohammad Matroud; POPOVA, Olha (Theoretical and Practical Research in Economic Fields, 2025)
By means of an input-output model, this study seeks to identify the most influential sectors in the Jordanian economy based on the value and direction of their multiplier effects. The analysis is based on the third 73 sector 2016 input-output table released by the Jordanian Department of Statistics as its core dataset. Through the use of this framework, the research identifies the key industries capable of stimulating production growth, stimulating income generation, and fostering employment creation, given the current macroeconomic backdrop, i.e. high levels of poverty and unemployment. The results show that production and infrastructure sectors have highest total and net multipliers, respectively, reflecting their significant position in intersectoral relations and in boosting aggregate demand. These findings are a reference base to set investment and resource allocation priorities in policy making. The originality of the work lies on a revised interindustry analysis applied on Jordan's current economy dimensions pertinences and problems, in a way different from the previous approaches, which were more generalists. The study is limited in that it is bound to the timescales of the data available and the poor representation of informal economic activities. However, the results also have practical use for economic planning and structural policy and more widely in societal terms regarding the capacity of each sector for employment generation and regional equalization.